Vocational Education Revolution: Systematic Analysis of Augmented Reality Implementation in Technology and Vocational Learning - ‘Ariqsyah, Muhammad; Maksum, Hasan; Purwanto, Wawan; Huda, Asrul; Giatman, M (JETL (Journal of Education, Teaching and Learning), 2025)
This study systematically examines the implementation of Augmented Reality (AR) technology in the context of technology and vocational education during the period 2020-2025. Through a Systematic Literature Review (SLR) of 280 articles obtained from the ScienceDirect database, this study analyzes trends, methodologies, effectiveness, challenges, and opportunities for AR development in vocational learning. Key findings show a significant increase in the adoption of AR to improve the practical competencies of vocational students, especially in the fields of mechanical engineering, electronics, construction, and health. The analysis also revealed that the implementation of AR can improve student engagement, understanding of complex technical concepts, and the development of psychomotor skills. Nonetheless, challenges such as development costs, technology infrastructure, and educator training needs are still obstacles that need to be overcome. This study provides a comprehensive conceptual framework for the implementation of AR in vocational education and recommendations for future research as well as practical implications for vocational education providers.